Development and Evaluation of Massive Open Online Courses to Support Sustainable Learning for Informatics Teachers in Indonesia - Sulistiyarini, Dewi; Feladi, Vindo; Sabirin, Febrianto; Wahab, Noorjima Abd (Jurnal Pendidikan MIPA, 2025)
Informatics teachers in West Kalimantan face challenges in continuously updating their knowledge and pedagogical skills due to the rapid development of information technology and the implementation of a new curriculum that makes informatics compulsory. However, there is a lack of structured learning facilities to support their professional development. This study aims to develop and evaluate the feasibility of a Massive Open Online Course (MOOC) as a platform for continuous professional development of informatics teachers. This study employed a Research and Development approach using the ADDIE model involving two design experts, two system experts, and thirty informatics teachers. The MOOC was developed using the Moodle platform and integrated features aligned with teacher needs, UI/UX design, and expert validation, including diverse learning materials, quizzes, and discussion forums. Validation was carried out by experts, while teacher responses and learning outcomes were evaluated using questionnaires and pre-test/post-test analysis. Expert validations indicated that the MOOC was of very high quality, and teacher responses showed strong enthusiasm and satisfaction. Furthermore, post-implementation evaluation revealed significant improvements in both teachers’ knowledge and motivation (p-value less than 0.05). The normalized gain score reached 47.91% for competence, indicating a moderate improvement, and 29.96% for motivation, indicating a low improvement. This demonstrates that the MOOC effectively supports both cognitive and affective growth. The developed MOOC has proven to be both feasible and effective as a professional learning platform for informatics teachers. Beyond improving knowledge and motivation, it offers scalability and accessibility, providing a sustainable solution for professional development in remote or under-resourced regions. Its implementation has the potential to bridge gaps in continuous education, particularly in Indonesia’s 3T (frontier, outermost, disadvantaged) areas, while also serving as a pilot model for other subject teachers.    Keywords: MOOC, lifelong learning, teacher competencies, informatics teachers.